Geographic Information System for Schools Mapping in Tugumulyo District, Musi Rawas Regency - Hutrianto Hutrianto; Baibul Tujni (Universitas Bina Darma, 2019)
School is institution that provide educational services to the community formed by the government in the form of organizational means to educate the nation's life. To guarantee the implementation of good education and in accordance with regulations set by the government, each school or school educational institution must follow accreditation. The spread of school locations certainly makes it difficult to access for assessors when they are going to do an accreditation assessment. In addition, other constraints experienced by the unavailability of school location information can be used as a reference for assessors in the accreditation assessment process. Under these conditions, it will certainly cause problems or obstacles in the accreditation process such as (1) the accreditation assessment process is not on schedule, (2) inaccurate assessment of the schedule, and (3) the quality of the accreditation assessment itself. Based on these conditions, in this study the development of a school mapping geographic information system can be used as a means of information for assessors in conducting accreditation assessments. the results of research that has been done show that geographic information systems can provide information on the distribution of schools both middle and upper levels. The information system can also function properly based on test results